Psychosocial risk factors in women with double presence in times of Covid 19 (Hilo Analítico, 2022)
Justification: due to the increase in psychosocial risk factors derived from health contingency measures, such as confinement that led to the performance of various tasks in a single space, with women being the most vulnerable population against aspects such as work overload. Objective: To identify which are the psychosocial risk factors in women with double presence in times of pandemic. Ethical aspects: this research is carried out under the framework of informed consent, making clear the academic objective of the study, data collection method, and duties and rights of the participant. Methodology: descriptive design of a qualitative order with a phenomenological approach, based on a semi-structured interview with a 51-year-old woman with double presence. Results: Each of the psychosocial risk factors was evidenced: Work content, work hours, workload, family and work relationship and double presence. Conclusions: The results obtained denote the enormous inequality gap that prevails at home and at work, and that revolves around a series of social stereotypes.